Laboratory rearing of wild Arctic cod Boreogadus saida from egg to adulthood. Issue 3 (1st February 2016) - Kent, D.; Drost, H. E.; Fisher, J.; Oyama, T.; Farrell, A. P.
Abstract : The techniques and protocols used to successfully capture, transport and breed Arctic cod Boreogadus saida, as well as to rear their larvae through to adulthood are summarized. Breeding B. saida will increase the opportunity to study this fish species, which is a critical part of the Arctic food web.